CYP2D6 copy number distribution in the US population - Beoris, Michelle (Pharmacogenet Genomics, 2016)
The cytochrome P450 2D6 (CYP2D6) gene is perhaps the most well characterized gene involved in drug metabolism and is known to have both gene duplication and deletion variants that are inheritable and stable. In a set of over 30 000 deidentified clinical samples we found that 12.6% of all patients tested had zero, one, or three or more copies of the CYP2D6 gene. On the basis of the combined frequency and impact of these variants, we believe that CYP2D6 copy number variation may account for the single most impactful genetic anomaly as it relates to pharmacogenetic directed therapies.